THE EFFECT OF SHORT-CIRCUIT FAULTS ON THE DIFFERENTIAL RELAY OF TRANSFORMER 1 AT KALIBAKAL SUBSTATION USING ETAP 19.0.01 - Novatilana, Anisa; Nasrulloh; Prasetyono, Rizki Noor (Program Studi Teknik Elektro Universitas Peradaban, 2025)
The differential relay is one of the protection components used to detect internal faults in transformers by comparing the incoming and outgoing currents within the protection zone. This study aims to analyze the effect of short-circuit faults on the operation of the differential relay using Electrical Transient Analyzer Program (ETAP) software. The method used is descriptive quantitative with a simulation-based approach using ETAP and binary logistic regression analysis. The results of the binary logistic regression test indicate that fault location and fault type do not significantly affect the relay operation decision, with a significance value of 0.989 and a Nagelkerke R Square of 0.016. These findings are consistent with the fundamental principle of differential relays, which focus on the difference between incoming and outgoing currents, rather than the fault position or fault type.